2022
DOI: 10.2147/prbm.s371254
|View full text |Cite
|
Sign up to set email alerts
|

How Does Parent-Adolescent Conflict and Deviant Peer Affiliation Affect Cyberbullying: Examining the Roles of Moral Disengagement and Gender

Abstract: Purpose With the widespread use of the Internet and mobile phone, cyberbullying has become a new type of bullying among adolescents. It is of great practical significance to explore the relevant factors affecting cyberbullying for prevention and intervention of adolescents’ cyberbullying. However, few studies have considered the effect of both the family and social factors on cyberbullying. Therefore, the current study examines whether the parent-adolescent conflict as a family factor and deviant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
2
6
0
2
Order By: Relevance
“…For example, Wojciechowski [53], in a longitudinal study using a sample of juvenile offenders, found that polyvictimization was related to violent offending, through moral disengagement and lack of impulse control. Moreover, other studies have observed that moral disengagement mediated the effect of exposure to family violence on bullying and cyberbullying [54][55][56][57]. However, there are no studies that examine the mediating role of moral disengagement in the relationship between early exposure to family violence and CPV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wojciechowski [53], in a longitudinal study using a sample of juvenile offenders, found that polyvictimization was related to violent offending, through moral disengagement and lack of impulse control. Moreover, other studies have observed that moral disengagement mediated the effect of exposure to family violence on bullying and cyberbullying [54][55][56][57]. However, there are no studies that examine the mediating role of moral disengagement in the relationship between early exposure to family violence and CPV.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothesis 3. We expect moral disengagement to mediate the relationship between early exposure to family violence (vicarious and direct exposure, independently) and CPV [53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…The third aim was to explore the relationship between the dimensions of perceived paternal and maternal warmth (warmth-communication and criticism-rejection) and CPV through different moral disengagement strategies. The results found in previous research show that moral disengagement mediates the relationship between an individual's family environment and aggressive and delinquent behaviors [47][48][49][50][51], including violent behaviors perpetrated against parents [54], and we expected that different moral disengagement strategies would mediate the effect of dimensions of perceived parental warmth during childhood on CPV. Our study showed that the dimensions of perceived parental warmth by the father and the mother have different indirect effects on CPV depending on whether the violence was directed toward the father or toward the mother.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, from this approach, moral disengagement could act as a mediating variable. Some studies have analyzed the effect of an individual's family environment, such as positive parenting [47], parental attachment [48], parent-adolescent conflict [49] or childhood maltreatment [50,51], on aggressive and delinquent behaviors through moral disengagement. In addition, the relationship between parental warmth and aggressive behavior has been mediated by moral disengagement, as suggested by some studies.…”
Section: Introductionmentioning
confidence: 99%
“…‫ﺘكﺎب‬ ‫�ﺎر‬ ‫اﻟتنبؤ‬ ‫إﻤكﺎﻨ�ﺔ‬ ‫ﻋن‬ ‫�كﻞ،‬ ‫اﻷﺨﻼﻗﻰ‬ ‫ام‬ ‫اﻻﻟتز‬ ‫و‬ ‫اﻷﺨﻼﻗﻰ‬ ‫ام‬ ‫اﻻﻟتز‬ ‫ﻋدم‬ ‫آﻟ�ﺎت‬ ‫ﺨﻼل‬ ‫ﻤن‬ ‫اﻻﻟكتروﻨﻰ‬ ‫اﻟتنمر‬ ‫ﻓبینمﺎ‬ ‫اﻷﺨﻼﻗﻰ.‬ ‫ام‬ ‫اﻻﻟتز‬ ‫ﻋدم‬ ‫آﻟ�ﺎت‬ ‫�ﺎﺨتﻼف‬ ‫اﺴﺎت‬ ‫اﻟدر‬ ‫ﺘﻠك‬ ‫ﻨتﺎﺌﺞ‬ ‫اﺨتﻠﻔت‬ ‫�ن‬ ‫و‬ ‫اﺴﺔ‬ ‫در‬ ‫ﺘوﺼﻠت‬ (Robson & Witenberg, 2013) ‫ﺘكﺎب‬ ‫�ﺎر‬ ‫اﻟتنبؤ‬ ‫إﻤكﺎﻨ�ﺔ‬ ‫إﻟﻰ‬ ‫اﺴﺔ‬ ‫در‬ ‫ﺘوﺼﻠت‬ ‫اﻟﻠوم،‬ ‫�ﺴنﺎد‬ ‫و‬ ‫اﻟمسؤوﻟ�ﺔ‬ ‫ﻨشر‬ ‫آﻟیتﻲ‬ ‫ﺨﻼل‬ ‫ﻤن‬ ‫اﻻﻟكتروﻨﻰ‬ ‫اﻟتنمر‬ (Romera et al, 2021) ‫�د‬ ‫وﺘجر‬ ‫اﻗب‬ ‫اﻟﻌو‬ ‫وﺘشو�ﻪ‬ ‫ﻓﻰ‬ ‫اﻟمﻌر‬ ‫اﻟبنﺎء‬ ‫اﻋﺎدة‬ ‫أن‬ ‫إﻟﻰ‬ ‫ﻋﻼوة‬ ‫اﻻﻟكتروﻨﻰ.‬ ‫اﻟتنمر‬ ‫ﺘكﺎب‬ ‫�ﺎر‬ ‫داﻟﺔ‬ ‫ﻤنبئﺎت‬ ‫�ﺎﻨت‬ ‫اﻻﻨسﺎﻨ�ﺔ،‬ ‫اﻟصﻔﺎت‬ ‫ﻤن‬ ‫اﻟضح�ﺔ‬ ‫ذﻟ‬ ‫ﻋﻠﻰ‬ ‫اﺴﺎت‬ ‫در‬ ‫ﻨتﺎﺌﺞ‬ ‫أﺴﻔرت‬ ‫ك،‬ (Ak et al, 2022;Bartolo et al, 2019;Dou et al, 2020;Fang et al, 2020;Liang et al, 2022;Orue & Calvete, 2019;Wang et al, 2017;Wang et al, 2019;Yang et al, 2018;Zhang, 2021;Zhang et al, 2021;Zhou et al, 2019;Zych & Llorent, 2019;Zych et al, 2020 ‫اﻟمﻌﺎﻤﻠﺔ‬ ‫ﻫذﻩ‬ ‫ﯿتﻠﻘون‬ ‫ﻻ‬ ‫اﻟذﯿن‬ ‫�ﺄوﻟئك‬ ‫ﻨﺔ‬ ‫ﻤﻘﺎر‬ ‫�سﻬوﻟﺔ‬ ‫اﻟتنمر‬ ‫ﺴﻠو��ﺎت‬ ‫ﻓﻰ‬ (Walrave, Ponnet, Vanderhoven, Haers & Segaert, 2016) .…”
unclassified